Floral Biology and Fruit Development in Varikka and Koozha of Jack (Artocarpus heterophyllus Lam.) - Tessy Joseph (Department of Agricultural Botany, College of Horticulture, 1983)
The present investigations were carried out in the Department of Agricultural Botany, College of Horticulture, Vellanikkara during the year 1981-82. The object was to study the pattern of flowering, floral biology, fruit set, fruit drop and fruit development in jack types ‘Varikka’ and ‘Koozha’. The studies were conducted on 14 trees, eight belonging to ‘Varikka’ and six belonging to ‘Koozha’, which were about 50 years old, and maintained under uniform management conditions, located at the Instructional Farm and Research Station, Mannuthy. There was difference in pattern of male and female spike production. The male spike production commenced from October and extended for a period of five months, while female spike production was confined to only three months, starting from late November. The peak time of male and female spike production was in December-January. The inflorescence in jack is a catkin. The process of development of spike took on an average 33.7 days in male and 59.7 days in female. The individual flowers were radially arranged on a fleshy peduncle. The perianth tubes of male flowers were free from each other while that of female were fused in the middle. In a male spike anthesis continued upto 5 to 7 days, on a particular day, anthesis started at 6 am and reached a peak between 12 noon and 4 pm and continued upto 6 pm. The emergence of stigma on a female spike was highly eratic and continued for about three weeks. The peak time for anther dehiscence was between 6 pm and 7 pm, on the day of its emergence. In a female spike complete fading away of stigma occurred in 21 to 30 days after anthesis started. The percentage pollen fertility ranged from 89 to 93 per cent, and mean pollen diameter ranged from 16 to 22 u. 10 per cent sucrose-1 per cent agar media was found to be the best media for pollen germination. The viability of pollen was lost completely within 24 hours after dehiscence. The chief agent of pollination was found to be wind. Fruit set under natural conditions was 83.33 per cent. Hand pollination gave decreased set. Apomictic fruit development was absent in Jack. The percentage fruit drop ranged from 30 to 40 per cent. The whole spike after anthesis developed into a large composite fruit which was a ‘false fruit’, with the persistent perianth forming the bulk of the fruit. Among the flowers on a spike few showed normal development rest got aborted. The time required for full development of fruit ranged from 100 to 138 days, the growth showed a sigmoid pattern. The two types ‘Varikka’ and ‘Koozha’ did not vary significantly for most of the flower and fruit characters except for the texture of flakes; ‘Varikka’ had hard flakes while ‘Koozha’ had softy mushy flakes.